Infâncias e(m) refúgio: o cotidiano de crianças refugiadas - Nagem, Jessica Cunha de Oliveira (Universidade Federal de São Carlos, 2024)
Each year, the number of people forcibly displaced from their homes and who, therefore, seek refuge in other countries, increases significantly, making the current situation experienced by refugees recognized as one of the greatest humanitarian crises of all time. Nevertheless, the number of studies on this topic, especially on Brazilian soil, is incipient and inexpressive, compared to the number of people affected by this problem. Approximately half of the refugee population is composed of children who experience the situation of forced displacement accompanied or not by their families, which is a marker of vulnerability related to the mental health of this population. The refuge situation imposes ruptures in the daily experience of the people who experience it, including children, however, little consideration has been shown for them in the production of knowledge about the reality they go through. The general objective of this study was to identify the perspectives of children in refugee situations about their daily lives, focusing on the act eating, the act of playing and the act of dwelling. This was qualitative research of exploratory nature, whose main methodological resource was immersion in field research, using creative methods for the production of data that used everyday activities common to childhoods (games, production of collages and drawings), in addition to recording in a field diary, photographs and participant observation. Fourteen Afghan children between 5 and 10 years old, who were in a situation of refuge on Brazilian soil and were welcomed in an institution in the state of São Paulo, participated in this research. It should be noted that, when mentioning the refugee situation, both refugee children and those awaiting recognition of the refugee status are included. The results of this research were presented based on the recordings in a field diary, photographs and drawings made by the children themselves. The data obtained was analysed based on a reading guided by Bardin's Thematic Analysis Technique (2011), with special attention to the children's own reading regarding their activities. The research participants associated the three categories explored with both Brazilian aspects and aspects of their native country, expanding their daily experience from the current context. The presence of their homes was diverse, and the participants signalled as home both the place where they are in refuge and the place from where they left. They associated to the act of dwelling: aeroplane, Afghan and Brazilian houses and, mainly, people, presenting the human aspect, especially their families, as a dwelling space. To the act of eating, the children explored Brazilian food and Afghan food and, to the act of playing, they associated meetings between their peers, meetings in order to carry out the research activities and different and spontaneous moments of daily life. The participants demonstrated a search for the collective throughout this research, which also brought as results the complex relationship of the participants with the public educational system; capable of providing clues for the effective reception of the refugee population to the Brazilian educational system, as well as reflections on a daily grammar potentially welcoming to childhoods and/in refuge. Finally, the research revealed the importance of considering refugee childhoods based on their own narratives and suggests that other studies should tackle this topic.
Childhoods and refuge: the daily life of refugee children
Keywords: Infância; Refugiados; Crianças refugiadas; Terapia ocupacional; Cotidiano; Childhood; Refugees; Refugee children; Occupational therapy; Daily life; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE